A maldição da individuação: reflexões sobre o entrelaçamento prazer-medo e a expressão literária - Franciscatti, Kety Valéria Simões (2005)
This PhD research, on the basis of Critical Theory of Society, has the target to show the paradox of the curse of the individuality the sufferings lived between the (im)possibilities of other s suffering and to become different as a result of the culture failure which impeaches and cut off the formative movement of the love, focusing its thought in the relation of pleasure and fear and in the potentialities of literary expression. The argumentations about these two focus can be described in two perspectives which are intersected. The first tries to put in evidence the sexual repression damage and the erotic renounce to the process of the person s formation, to raise the problems and to think about the destruction manifestations as a result of the cultural impeachments to formative movement of love, of no-fruition of the beauty, the mutilation of the senses, the foolishness of the reasoning and of the consequent hardness of the ego. The second focus tries to show the esthetic experience provided by literature (from the artist and from the receptor) as a privileged condition of contact and thought about the object of this research (the moment of the curse of the individuality), considering potentially the literary expression, without decreasing it to the psychologism, in three dimensions at the same time: as a testimony and manifestation of the unjustified sufferings, as resistance, because it contains hate (destruction of the object), and possibilities of changes the existent, because they can keep small parts which can lighten some exits from this state, alternatives to go further the destruction. The theoretical formulations from the authors of Frankfurt Adorno, Horkheimer and Marcuse; Freud; and selected literary parts from Portuguese language writers: from Brazil, Clarice Lispector and Caio Fernando Abreu; from Portugal, Fernando Pessoa (he himself and under the heteronames of Alvaro de Campos and Bernardo Soares) and José Saramago are predominantly systematized. However, the given status to the writers is different. The Lispector literary parts are in the center of the thoughts; the interlocution of other mentioned writers is aimed, emphasizing Abreu, in order to construct the discussion and the consecution of the proposed target. Also because of this reason, there is a certain relevance in the presence of another writer: Fernando Sabino, with whom Lispector exchanged letters during some years. There is no intention to discuss the work of these writers in its totality, the emphasized parts (tales, novels, poetry and letters) are worked as a representation of artistic expression in the dimensions mentioned before. With this announced target, the proposal of these argumentations and these indicated thoughts (theoretical and literacy), is intended to show the thesis that the curse of the individuality is related to, in its basis, the mutilation of the movement of love caused by cultural impeachments which damage the senses and the reasoning harmed formation which makes more difficult the installing of fruition as a way of life, which sticks the understanding and the possibility of beauty to face the sufferings mostly unjustified, in face of the existing material conditions and in that moment expressed in the literary work by the artistic expression, provides fundamental experiences to the contention, the sensitive thought and the search for possible exits from the destruction state and from the barbarous ness order, once in the art some, representing every men (among scars and fragments) expressing the prison between the desire and not getting to live, accomplish works in a desperate hope of, finally, having a free and happy life.